The influence of genetic polymorphisms in drug metabolism enzymes and transporters on the pharmacokinetics of different fluvastatin formulations - Qian Xiang; Weidang Wu; Nan Zhao; Chuan Li; Junyu Xu; Lingyue Ma; Xiaodan Zhang; Qiufen Xie; Zhuo Zhang; Jiancheng Wang; Weiren Xu; Xia Zhao; et al. (Elsevier, 2020)
The purpose of the present study was to investigate the impact of genetic polymorphism on fluvastatin pharmacokinetics. In addition, we compared the fluvastatin pharmacokinetics differences between extended-release (ER) 80 mg tablet and immediate-release (IR) 40 mg capsule in terms of drug metabolism enzyme and transporter genetic polymorphisms. In this open-label, randomized, two-period, two-treatment, crossover study (n = 24), effects of ABCG2, SLCO1B1, ABCB1, CYP2C9 and CYP3A5 polymorphisms on the pharmacokinetics of fluvastatin were analyzed. The administration dosage for IR 40 mg and ER 80 mg were twice and once daily, respectively, for total 7 d. Blood samples for pharmacokinetic evaluation were taken on the 1st and 7th d. The lower exposure following ER was observed. For ER tablets, SLCO1B1 T521C genotype correlated with AUC0-24 of repeat doses (P = 0.010). SLCO1B1 T521C genotype had no statistically significant effect on AUC0-24 of IR capsule of fluvastatin after single or repeated doses. In vitro study demonstrated that when the concentration of fluvastatin was low (< 1 µmol/l), the uptake of fluvastatin in the HEK293-OATP1B1 with SLCO1B1 521TT (Km=0.18 µmol/l) was faster than that with SLCO1B1 521CC (Km=0.49 µmol/l), On the other hand, when concentration reached to higher level (> 1 µmol/l), transport velocity of fluvastatin by HEK293-OATP1B1 with SLCO1B1 521TT (Km = 11.4 µmol/l) and with SLCO1B1 521TCC (Km=15.1 µmol/l) tend to be the same. It suggests that the increased effect of SLCO1B1 T521C genotype on ER formulation of fluvastatin was mainly caused by lower blood concentrations. We recommend that formulation should be incorporated into future pharmacogenomics studies. Keywords: Genetic polymorphisms, SLCO1B1, Fluvastatin, Immediate-release, Extended-release